The Influence of Interactive Method toward the Students’ Speaking Skills at the SMP Santo Thomas 3 Medan - Siska Julinda Yani Zega; Karisma Erikson Tarigan; Fiber Yun Almanda Ginting (English Language Education Department, Universitas Majalengka, 2023)
In this study, the writer focused on the use of interactive methods on the speaking skills of class VII students of SMP Santo Thomas 3 Medan with the aims of 1) to determine whether the interactive method has enough influence on the speaking skills of class VII students of SMP Santo Thomas 3 Medan and 2) to find out how enthusiastic are students in learning speaking after they are thought by interactive methods. The type of research used is Classroom Action Research (CAR). The results of this study indicate that: 1) the interactive method affects students' speaking skills, increasing the average score of students' pre-test by 56.03%, formative test by 61.35%, and post-test by 72.32%. 2) It can be seen that the student's response to the interactive method on students' speaking skills is very positive. The percentage of the questionnaire results in statement number 3 there were 23 students 82% who agreed to the statement that students became more enthusiastic about speaking English in learning to speak English using material describing objects using interactive methods, and 4 students 14% strongly agreed. It can be concluded that the application of the interactive method positively influences students' speaking ability, which is the achievement of students' speaking skills.